2018
DOI: 10.1016/j.arabjc.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of palladium nanoparticles using gum ghatti (Anogeissus latifolia) and its application as an antioxidant and catalyst

Abstract: A facile and green route for the synthesis of palladium nanoparticles from palladium chloride was developed using non-toxic, renewable plant polymer, gum ghatti (Anogeissus latifolia), as both the reducing and stabilizing agent. The generated nanoparticles were characterized with UV-visible spectroscopy (UV-vis), dynamic light scattering (DLS), transmission electron microscopy (TEM), and X-ray diffraction (XRD) techniques. The formation of palladium nanoparticles was confirmed from the appearance of intense br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(74 citation statements)
references
References 36 publications
(54 reference statements)
7
65
1
Order By: Relevance
“…The absorbance (At) at λ 664 nm (which is proportional to the concentration of MB) in each minute after the addition of catalyst is noted and pseudo‐first order rate constant (k app ) for decolorization of MB was determined by plotting ln(A t ) against time (Figure ). The apparent rate constant calculated for PNA‐20Ag catalyzed reduction of MB was 0.1686 min ‐1 , and the result is comparable to some reported catalytic studies …”
Section: Resultssupporting
confidence: 88%
“…The absorbance (At) at λ 664 nm (which is proportional to the concentration of MB) in each minute after the addition of catalyst is noted and pseudo‐first order rate constant (k app ) for decolorization of MB was determined by plotting ln(A t ) against time (Figure ). The apparent rate constant calculated for PNA‐20Ag catalyzed reduction of MB was 0.1686 min ‐1 , and the result is comparable to some reported catalytic studies …”
Section: Resultssupporting
confidence: 88%
“…The PdNPs have enormous catalytic potential in various organic transformations, including Suzukicross, Mizoroki-Heck, Stille, and Sonogashira coupling reactions. [9][10][11] However, the application of PdNPs in the biomedical field is yet to be adequately investigated, although the green-synthesized PdNPs possess remarkable antioxidant 12,13 and antimicrobial activities. 12,14 Plant-derived PdNPs seem to have potential for application in cancer therapy because these compounds are also toxic to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, the application of PdNPs in the biomedical field is yet to be adequately investigated, although the green-synthesized PdNPs possess remarkable antioxidant 12,13 and antimicrobial activities. 12,14 Plant-derived PdNPs seem to have potential for application in cancer therapy because these compounds are also toxic to cancer cells. 15,16 In this study, we demonstrated a simple one-step green process to synthesize PdNPs using Camellia sinensis (white tea [W.tea]) extract from unfermented young tea leaves or unopened buds.…”
Section: Introductionmentioning
confidence: 99%
“…Kora and Rastogi have investigated that Pd nanoparticles have no antibacterial activities. 37 The zones of inhibition of Cu nanoparticles against B. thuringiensis and S. aureus were found to be at 14±0 and 16±0 nm, respectively, as shown in Figure S2A and B. The positive control plate loaded with ofloxacin has a zone of inhibition at 16 mm.…”
Section: Comparative Antibacterial Properties Of Cu Pd and Their Bimmentioning
confidence: 96%